Gender Differences in Knowledge and Attitude towards HPV and HPV Vaccine among College Students in Wenzhou, China - Gang Chen; Biao Wu; Xuchao Dai; Mengqi Zhang; Yupeng Liu; Hong Huang; Kun Mei; Zhigang Wu (Vaccines, 2021)
Objective: This study aimed to determine human papillomavirus (HPV)-related awareness and willingness to receive HPV vaccination among college students, in Wenzhou, and its associated factors. Methods: A cross-sectional epidemiological study was conducted among college students in Wenzhou to investigate their knowledge, attitude, and factors affecting their willingness to receive HPV vaccination. Results: A total of 1035 questionnaires were collected, of which 1002 were valid (males: 374, females: 628). In total, 904 (90.2%) college students had heard of HPV, with a lower rate among males than females (85.3% vs. 93.2%, p < 0.05) and 693 (69.2%) had heard of the HPV vaccine, with a significantly lower rate among males than females (53.7% vs. 78.3%, p < 0.05). Overall awareness of HPV and HPV vaccine among males and females was moderate, with lower awareness among males. A total of 55.9% of males and 80.4% of females indicated that they would be willing to receive the HPV vaccine, a significant difference (p < 0.001). The price, safety of HPV vaccine, and lack of knowledge about HPV and HPV vaccine were the major barriers to HPV vaccination for college students. Compared to females, inadequate knowledge of HPV was the main barrier factor for HPV vaccination among male college students. Conclusions: The overall knowledge level of males is lower than that of females. For male college students, providing more knowledge about HPV infection is helpful to promote their willingness to vaccinate. It is necessary to promote HPV-related knowledge for male and female college students, respectively.